TRIMA DIA PAS DIPANDANG:TRICHODERMA DENGAN MEDIA AMPAS TEBU DICAMPUR DENGAN PUPUK KANDANG SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT DI KENAGARIAN LAWANG, AGAM - Eka Candra Lina; Amalina Wahyuni; Trisna Ayu Wandira; Apdi Masela Mirsal; Ronauli Fernandes S (BULETIN ILMIAH NAGARI MEMBANGUN, 2018)
Nagari Lawang is a nagari in the area of Agam Regency, West Sumatra which is known as the center of sugar cane. Sugar cane plants that have been processed into saka sugar or other products will produce waste in the form of bagasse which is only used for combustion and thrown away without being used. The purpose of this community service activity is to transfer knowledge and technology from the higher education environment to the public regarding the use of bagasse waste, reduce environmental pollution and open business opportunities for the local community. This activity was carried out with four general stages, namely program introduction introduction, field implementation, program monitoring, and evaluation. The implications of the results of this activity are the knowledge and skills of the community in breeding Trichoderma mushrooms with bagasse media and application of Trichoderma mushrooms with manure on agricultural crops.